A Rare and Challenging Presentation of Empyema Necessitans/Necessitasis Leading to Brachial Plexopathy - Abufaied, Mohamad (Cureus, 2020)
Empyema necessitasis (EN) also referred to as empyema necessitans (EN) is a rare complication of empyema that can involve soft tissues outside the pleural cavity and can lead to brachial plexus injury. Although, brachial plexus injury most commonly occurs as a result of trauma, inflammation, or malignancies, but it has been rarely seen in EN. We are reporting a rare and challenging case of empyema necessitasis (EN) causing impingement of brachial plexus in a 42-year-old, type 2 diabetic patient, who initially presented to the hospital with left-sided pleuritic chest pain and acute onset of left upper limb weakness. Urgent CT brain ruled out an acute neurological insult. Chest radiograph and contrast-enhanced CT thorax revealed left-sided loculated effusion. MRI of the left upper limb showed impingement of brachial plexus by the inflammatory process of surrounding effusion. Ultrasound-guided aspiration of the encapsulated fluid was performed and culture analysis of the fluid was remarkable for Prevotella oris (sensitive strain) growth. After drainage of the infected fluid and with a prolonged course of antibiotics, the patient's neurological symptoms improved significantly. Hospital course was uncomplicated and further follow-up was unremarkable for any deterioration. Our objective is to emphasize on the prompt management with close follow-up in EN, which can present with life-threatening complications as seen in our case. Any delay can compromise the patient’s health. As per our limited knowledge, this case has not been reported in the literature.